1970
DOI: 10.3126/narj.v6i0.3366
|View full text |Cite
|
Sign up to set email alerts
|

Role of weather on <i>Alternaria</i> Leaf Blight Disease and its effect on Yield and Yield Components of Mustard

Abstract: Alternaria leaf blight disease caused by Alternaria brassicae in mustard (Brassica juncea (L) Czern and Coss) was studied in two crop seasons, 1992 and 1993 in Nepal at Nawalpur, Sarlahi (Tarai) and Khumaltar, Lalitpur (mid hill). At Nawalpur, epidemics of the disease was recorded for both seasons. Weather conditions like humidity, temperature and frequent rainfall played key role for the epidemics. In experimental fields, the disease appeared first in mid-December when the relative humidity was more than 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 11 publications
4
44
0
1
Order By: Relevance
“…Many scientists worked on control Alternaria leaf blight of brassica by different plant extracts and chemicals. Our results are in agreement with [8,13] who checked the efficacy of plant extracts obtained from garlic, neem leaf, ginger and onion bulb against Alternaria brasicae. It was observed that the application of plant extracts show significant result to increase the seed germination as compare to untreated control.…”
Section: Results and Discussion:-supporting
confidence: 82%
“…Many scientists worked on control Alternaria leaf blight of brassica by different plant extracts and chemicals. Our results are in agreement with [8,13] who checked the efficacy of plant extracts obtained from garlic, neem leaf, ginger and onion bulb against Alternaria brasicae. It was observed that the application of plant extracts show significant result to increase the seed germination as compare to untreated control.…”
Section: Results and Discussion:-supporting
confidence: 82%
“…However, maximum temperature, maximum RH, number of rainy days and wind velocity were found to be statistically significant with respect to disease development which supports the findings of Cova and Rodriguez (2001), Delahaut and Walt (2004) and Shrestha et al, (2005) (Table 4). The maximum temperature alone contributed 49.28% towards the disease development followed by minimum temperature (23.88%) and then wind velocity (21.82%).…”
Section: Resultssupporting
confidence: 79%
“…Average yield loss in the range of 32-57 per cent due to Alternaria blight has been reported from Nepal (Shrestha et al, 2005). Besides India, disease is reported to be of major economic importance in Australia, France and Poland and of moderate importance in Canada and United Kingdom (Sharma and Kolte, 1994;Verma and Saharan, 1994;Barman and Bhagavati, 1995).…”
Section: Resultsmentioning
confidence: 99%